Challenges of Childhood TB/HIV Management in Malawi - Poerksen, G (Malawi Medical Journal, 2007)
The diagnosis and management of childhood tuberculosis (TB) are major challenges in countries such as Malawi with high incidence of TB and human immunodeficiency virus (HIV) infection. Diagnosis of TB in children often relies only on clinical features but clinical overlap with the presentation of HIV and other HIV-related lung disease is common. The tuberculin skin test (TST), the standard marker of M. tuberculosis infection in immune competent children, has poor sensitivity in HIV-infected children and is not usually available in Malawi. HIV test should be routine in children with suspected TB as it improves clinical management. HIV-infected children are at increased risk of developing active disease following TB exposure which justifies the use of isoniazid preventive therapy (IPT) once active disease has been excluded but this is difficult to implement and appropriate duration of IPT is unknown. HIV-infected children with active TB experience higher mortality and relapse rates on standard TB treatment compared to HIV-uninfected children, highlighting the need for further research to define optimal treatment regimens. HIV-infected children should also receive appropriate supportive care including cotrimoxazole prophylaxis and anti-retroviral treatment (ART) if indicated. There are concerns about concurrent use of some anti-TB drugs such as rifampicin with some ARTs.